VOCATIONAL EDUCATION, YOUTH AND WORK: CONTRADICTIONS IN RELATION TO CONTEXTUALIZED EDUCATION IN THE SEMI-ARID REGION OF CEARÁ - Silva, Francisco Elitom Rodrigues da; Falcão Sobrinho, José; Falcão, Cleire Lima da Costa (Revista Territorium Terram, 2026)
The growing unemployment among the younger segments of society, in the current context of a globalized world, is not only a regional phenomenon but a global one. The number of young people aged between 18 and 24 who neither work nor study has increasingly risen, causing negative impacts on local economies. Faced with the challenges of addressing the shortage of qualified labor to meet local and regional market demands and ensuring that new generations are properly trained for this purpose, vocational education in Ceará, integrated with full-time secondary education, has emerged as a public policy aimed at integrating young people from Ceará into the labor market and promoting regional economic development. From this perspective, this study sought to understand, through an empirical analysis of factual reality, the relationship between vocational education, youth, and employment in the semi-arid territory of Reriutaba-CE, based on a holistic-phenomenological approach associated with the geosystem framework in addressing the object of study. The results indicate that vocational education functions primarily as a means of preparing students for the ENEM and/or for the local labor market, generally in areas different from their original technical course, as most students aspire to other professional fields. This reveals a significant distance from the study of local reality, that is, from a contextualized education grounded in the semi-arid region.